STATIC CARBONATE RESERVOIR MODELLING AND ESTIMATION HIDROCARBON RESERVES OF JK INTERVAL, CIBULAKAN ATAS FORMATION, MENDEZ FIELD, NORTHERN WEST JAVA BASIN - Hayyu Tiffani, Resha
Mendez Field is in development stage administratively located in West Java Province and part of Northern West Java Basin, encompassing an area 11,9 x 4,2 km. This field located in Jatibarang Sub-Basin which associated with normal fault structure that has north east-south west orientation due to Meratus subduction in Late Cretaceaus and the formation of a new magmatic pathway during Miocene to Pliocene-Pleistocene. The reservoir in Mendez Field is in the Upper Cibulakan formation with a focus on JK reservoir intervals. This study aims to understand the geological conditions of the research field, determine reservoir characteristics such as depositional facies, distribution and reservoir properties, and the prospect of hydrocarbons in the JK reservoir. The data used consisted of 3D seismik data, core rock descriptions, wire log data, and perforation data. The methods used in the analysis are stratigraphic sequences, reservoir property analysis, geological structure analysis, static reservoir modelling, and estimation of hydrocarbon reserve volumes. Based on the characteristics of core rocks description, the study interval was arranged into 3 lithofacial units, namely Floatstone, Foraminifera Packstone to Wackestone dan Red Algae Foraminifera Packstone to Wackestone. The Upper Cibulakan Formation at Mendez Field is deposited in shallow marine environments. The research interval has facies associations such as normal platform-interior marine, inter reef and patch reef. Based on the results of property reservoir analysis, facies that have good reservoir quality is patch reef facies. The reservoir modelling results based on the stochastic method approach and volumetric hydrocarbon calculations concluded that there are prospects hydrocarbons at JK reservoir intervals with STOIIP of 490,855 MSTB and GIIP of 0,6 TCF.